Gallium-67 Citrate Scan in Extrapulmonary Tuberculosis - Lin, Wan-Yu; Hsieh, Jih-Fang (Nuklearmedizin - NuclearMedicine, 1999)
Aim: Whole-body gallium scan was performed to evaluate the usefulness of gallium scan for detecting extrapulmonary tuberculosis (TB) lesions. Methods: Thirty-seven patients with extrapulmonary TB were included in this study. Four patients were found to have two lesions. Totally, 41 lesions were identified, including 19 TB arthritis, 8 spinal TB, 5 TB meningitis, 3 TB lymphadenopathy, 2 TB pericarditis, 1 TB peritonitis, 1 intestinal TB, 1 skin TB and 1 renal TB. Results: Of the 41 extrapulmonary TB lesions, gallium scan detected 32 lesions with a sensitivity of 78%. All the patients with TB meningitis showed negative gallium scan. When the five cases of TB meningitis were excluded, the detection sensitivity of gallium scan increased to 88.9% (32/36). Conclusion: Our data revealed that gallium scan is a convenient and useful method for evaluating extrapulmonary TB lesions other than TB meningitis. We suggest that gallium scan be included in the clinical routine for patients with suspected extrapulmonary TB.
Keywords: Gallium-67 citrate scan; tuberculosis; extrapulmonary